Measuring the Classification of Digital Natives use Digital Natives Assessment Scale: The Implementation on Pre-Service Physics Teachers in Banten-Indonesia and Its Implications - Yudi Guntara; Indri Sari Utami (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
Education in the digital era had shifted conventional learning methods to digital technology-based learning. Likewise with students have to be faced by pre-service physics teachers who have entered the generation of digital natives. However, is it true that the concept of digital natives exists? Moreover, whether pre-service physics teachers belong to that generation? Therefore, the objective of this study was to prove the construct validity of the Digital Natives Assessment Scale using data from pre-service physics teachers in Banten Province, Indonesia. And follow-up analysis is used to find the relationship between digital natives' status and pre-service physics teacher technology mastery. This study used a quantitative approach with the correlational method. The type of correlation research chosen was Confirmatory Factor Analysis (CFA). The instrument used was a Digital Natives Assessment Scale (DNAS) questionnaire consisting of 21 items and four factors, measured using a 7-point scale. The results showed that this study could not prove the 4-factor DNAS model for pre-service teacher participants in Banten Province based on the results of the CFA. And there was no relationship between the status of digital natives and the level of technology mastery of pre-service teachers based on Pearson correlation analysis. So it can be concluded that using a sample of student-teacher candidates in Indonesia, the 4-factor DNAS cannot be proven construct validity. However, this decision is not final but should be tested on a larger scale to show DNAS matches.